The Impact of Vitamin D and Omega-3 Fatty Acid Supplementation on Muscle Health, Physical Performance, and Sarcopenia Prevention – A Review of Studies - Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika; Robak , Jakub; Telega , Stanisław; Bollin , Paweł; Szymczak, Urszula; Lachór, Wojciech Wiesław; Solarz, Monika Barbara; Piekarska, Julia; Solarz , Justyna Maria (Quality in Sport, 2025)
This review aims to assess the impact of vitamin D and omega-3 supplementation on muscle health, physical performance, and sarcopenia prevention. The analysis includes randomized controlled trials (RCTs), systematic reviews, meta-analyses, observational studies, and narrative reviews. Vitamin D regulates calcium metabolism, myocyte proliferation, and muscle regeneration, with deficiency linked to weakened strength and increased fall risk. However, the effects on physical performance are inconclusive, depending on 25(OH)D levels, dosage, and supplementation duration. Omega-3 fatty acids demonstrate anti-inflammatory effects, supporting muscle regeneration and function, particularly with resistance training. Some studies show beneficial effects on isometric strength, but their impact on muscle mass is inconsistent. Sarcopenia prevention studies suggest that supplementation, combined with physical activity, may be effective, though evidence on muscle mass remains unclear. In conclusion, vitamin D and omega-3 supplementation may support muscle function, particularly in deficient individuals, but further research is needed to assess their impact on physical performance and sarcopenia prevention. Long-term studies on optimal dosages, intervention duration, and synergistic effects with physical activity are required.